Autologous x-irradiated tumour cells and percutaneous BCG in operable lung cancer. Issue 8 (August 1982) - Stack, B H; McSwan, N; Stirling, J M; Hole, D J; Spilg, W G; McHattie, I; Elliott, J A; Gillis, C R; Turner, M A; White, R G
Abstract : To determine the value of specific immunotherapy with adjuvant BCG in operable lung cancer, the immunological and clinical results of serial postoperative injections of autologous irradiated tumour cells and BCG were compared with those of a single preoperative injection of BCG in two randomly selected groups of patients undergoing resection of their tumours. There was a significant rise in tuberculin skin reactivity from seven weeks to 11 months after operation in the treated group. Actuarial curves for survival and freedom from tumour recurrence and median survival times showed an advantage for the treated patients who had stage I tumours, but these differences were significant only at the levels p = 0.07 - 0.09. Survival and duration of freedom from tumour recurrence was greater in autograft-treated patients whose skin responded to a weak test dose of dinitrochlorobenzene (DNCB) after sensitisation with 2% DNCB than in control DNCB-positive patients (p = 0.02). There were no significant differences in the actual proportion of patients from each group surviving at two years. The results show that this form of specific immunotherapy with adjuvant may have a beneficial effect in patients with stage I tumours and those who become sensitised to 2% DNCB after the first exposure.